Food and Waterborne Disease in the Greater New York City Area Following Hurricane Sandy in 2012. (16th May 2016) - Bloom, Michael S.; Palumbo, Jillian; Saiyed, Nazia; Lauper, Ursula; Lin, Shao
Abstract: Objective: We aimed to evaluate residence in evacuation areas (storm areas) as a risk factor for food and waterborne disease (FWBD) associated with Hurricane Sandy flooding. Methods: We captured 9601 incident outpatient and inpatient FWBD hospital discharge diagnoses for residents of the greater New York City area. We used Poisson or negative binomial regression models to compare the covariate-adjusted risk for a FWBD diagnosis, pre-Sandy (10/28-11/09, 2001-2011) vs. post-Sandy (10/28-11/09, 2012), for residents of "storm" and "non-storm" areas. Results: Outpatient FWBD risk was lower for storm area residents after Hurricane Sandy (risk ratio [RR]=0.58, 95% confidence interval [CI]: 0.46-0.74), and varied by age, sex, and county. However, storm area residents 65 years of age or older experienced higher risk after Hurricane Sandy (RR=2.16, 95% CI: 1.11-4.19), albeit based on few cases. Inpatient FWBD risk was lower for non-storm area residents after Hurricane Sandy (RR=0.79, 95% CI: 0.66-0.95), and varied by age, race, and county, although there was no significant change for storm area residents (RR=0.86, 95% CI: 0.69-1.08). Those ≥65 years of age were also at lower risk for inpatient FWBD diagnosis, yet the effect was weaker for storm area (RR=0.89, 95% CI: 0.67-1.18) than for non-storm area residents (RR=0.68, 95% CI: 0.52-0.89). Conclusions: Hurricane preparation, mitigation, and response activities in the greater New York City area may have led to "protective" effects for FWBD. ( Disaster Med Public Health Preparedness . 2016;10:503–511)